Dampak Penggunaan Gadget Terhadap Perkembangan Anak Usia Pra Sekolah di TK Bina Putera Kecamatan Ciracas Jakarta Timur - Kumala, Anes Patria; Wahyuni, Nita Tri (NHM PRESS, 2024)
One of the impacts that occurs when young children are addicted to gadgets can be disruption to the child's growth and development. The World Health Organization (WHO) reports that 5-25% of preschool children suffer from developmental disorders. Gadgets make it easier for children to get access to information media and technology, so that children become lazy about moving and doing activities. They prefer to sit and enjoy the world inside the gadget. A situation like this will certainly affect the child's development, both in terms of physical, motor, psychological and social aspects of the child. Aimed study to determine the relationship between gadget use and development in pre-school children. The research design used was quantitative analytical observational with a cross sectional approach. The population used in this research was the students of Bina Putera Kindergarten, East Jakarta, totaling 42 children, sampling was carried out using total sampling. The instruments used in this research were the gadget intensity measurement questionnaire and the KPSP questionnaire. The statistical test in this research is chi-square. As a result of the research that has been carried out, it is known that 23 respondents (54.8%) had medium category gadget use, causing the development of the doubtful category for 25 respondents (59.6%). Data obtained from statistical results using the chi square test shows p-value = (0.016) < (0.05). There is a relationship between the use of gadgets and the development of pre-school children at Bina Putera Kindergarten, East Jakarta in 2024.